Exploration breakthrough and its significance of Gulong lacustrine shale oil in the Songliao Basin, Northeastern China - Jin, Zhijun; Liang, Xinping; Bai, Zhenrui (Energy Geoscience, 2022)
Lacustrine shale oil resources are abundant in many petroliferous basins in China. The shale oil formations are characterized by low API gravity, high viscosity, poor mobility, high clay content, low brittleness and etc. Exploration of lacustrine shale oil started relatively late in China, but its progress is very rapid and breakthroughs have been made successively. In this short communication, we introduced the most significant shale oil discovery which is made recently in the Qingshankou Formation of the Gulong sag in the Songliao Basin. Key exploratory wells including Guye 1H (GY1H), Yingye 1H (YY1H) and Guye 2HC (GY2HC) tested stable and high oil flow in shale reservoirs, revealing the relatively stable and high oil production capacity of shale in the Gulong sag of Daqing Oilfield. It marks a leap of petroleum theoretical recognition from lacustrine shale generating oil to producing oil and from the theory of traditional oil migration and accumulation to the theory of indigenous oil accumulation in organic-rich shale. Although lacustrine shale oil exploration and development still faces many challenges in China, its prospect is quite promising. [Display omitted] •Key exploratory wells reveal high oil production capacity of shale.•Gulong shale oil breakthrough opens scope for lacustrine shale oil exploration and development.•The prospect of lacustrine shale oil exploration and production in China is quite promising.